Surveying Kerman's Afazalipour Hospital clinical and educational staff`s points of view about the clinical decision support system designed for reducing the possibility of pulmonary embolism and deep vein thrombosis - Zh Agharezaei; SH Tofighi Sh; A Nemati; L AAgharezaei; K Bahaadinbeigi (Tehran University of Medical Sciences, 2013)
Background: This research aims to design and implement a software with the ability to identify patients who are facing the risk of pulmonary embolism and deep venous thrombosis instantly as well as the ability to send timely reminders for any prophylactic action. The main target is introduce a clinical decision- support system which could finally lead to preventing mortality and handicap cases caused by embolism and thromboses in patients who are confined to bed in hospitals. Materials and Methods: The software was designed using the Visual Basic.Net and SQL Server database. Afterwards the software was installed in the largest educational hospital of Kerman and a survey was conducted amongst the physicians using multiple questionnaires and interviews. Finally, the data were analyzed using the SPSS software. Results: The average score was 21.16 for the physicians and 20.76 for the nurses. T-Test results show that there is no significant difference between the total average score of the physicians and that of the nurses. Conclusion: The results have shown that both groups (physicians and nurses) have a positive viewpoint about the software therefore using the clinical decision support system can be effective in reducing the occurrence of pulmonary embolism and deep venous thrombosis through sending timely electronic alerts to the medical staff.